The application of finite element analysis to determine the optimal UIV of growing-rod treatment in early-onset scoliosis - Pan, Aixing; Ding, Hongtao; Wang, Junjie; Zhang, Zhuo; Zhang, Hongbo; Liu, Yuzeng; Hai, Yong (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives. To analyze the stress distribution in the proximal vertebral body and soft tissue of dual growing-rod (GR) with different upper instrumented vertebra(UIV) to determine the optimal UIV. Methods. A ten-year-old male EOS case treated with GR was selected. Based on spiral computed tomography (CT) scanning performed in 0.6 mm thick slices, a finite element model (FEM) of the preoperative state (M0, the original spine state ) of the patient was created. Subsequently, four models with different UIV fixations were numerically analyzed by FEM, including M1(UIV=T1, i.e. the upper-end vertebrae (UEV) of the upper thoracic curve), M2(UIV=T2), M3(UIV=T3) and M4(UIV=T4, i.e. the lower end vertebrae (LEV) of the upper thoracic curve). Displacement and maximum stress in the proximal vertebral body and soft tissue were measured and compared among the five models. Results. The spine model was fixed with the sacrum, and the gravity conditions were imposed on each vertebral body according to the research of Clin and Pearsall. The results are as follows：M4 model has the largest overall displacement, while M1 has the least displacement among the four models. Except M2, the maximum normalized stress of UIV increases with the downward movement of UIV. M1 has the lowerest annulus fibrosus stress and highest joint capsule stress, which is characterized by the vertebrae backward leaning, while M4 is the opposite. The supraspinous ligament stress of M3 and M4 is significantly higher than that of M1 and M2. This suggests that UIV downshift increases the tendency of the proximal vertebral bodies to bend forward, thereby increasing the tension of the posterior ligaments (PL). Conclusions. The UIV of the GR is recommended to be close to the UEV of the upper thoracic curve, which can reduce the stress of the proximalPL, thereby reducing the occurrence of proximal junctional kyphosis (PJK).